2020
DOI: 10.1021/acs.jpcb.0c04567
|View full text |Cite
|
Sign up to set email alerts
|

MARTINI-Compatible Coarse-Grained Model for the Mesoscale Simulation of Peptoids

Abstract: Peptoids (poly-N-substituted glycines) are a class of synthetic polymers that are regioisomers of peptides (poly-C-substituted glycines), in which the point of side-chain connectivity is shifted from the backbone C to the N atom. Peptoids have found diverse applications as peptidomimetic drugs, protein mimetic polymers, surfactants, and catalysts. Computational modeling is valuable in the understanding and design of peptoid-based nanomaterials. In this work, we report the bottom-up parameterization of coarse-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 101 publications
2
59
0
Order By: Relevance
“…Peptoids have not been studied with theoretical methods in the context of their membrane activity, but rather in the context of their applications in nanotechnology, e.g., the study by Jin et al, in 2016 [838]. Recently, a coarse-grained force-field created within the MARTINI framework [605] for peptoids was developed [839]. Nevertheless, the interactions between peptoids and membranes have been investigated experimentally [840].…”
Section: A Clear Case Of Drug Membrane Interaction As Mechanism Of Action-antimicrobial Agentsmentioning
confidence: 99%
“…Peptoids have not been studied with theoretical methods in the context of their membrane activity, but rather in the context of their applications in nanotechnology, e.g., the study by Jin et al, in 2016 [838]. Recently, a coarse-grained force-field created within the MARTINI framework [605] for peptoids was developed [839]. Nevertheless, the interactions between peptoids and membranes have been investigated experimentally [840].…”
Section: A Clear Case Of Drug Membrane Interaction As Mechanism Of Action-antimicrobial Agentsmentioning
confidence: 99%
“…[ 264 ] The simulations showed that DMAP molecules interfere with the monomer‐monomer interactions at the fiber ends by first penetrating in between the monomer porphyrin cores and then facilitating monomer dissociation from the fiber end. [ 264 ] Other supramolecular material systems that have been simulated with Martini include supramolecular block copolymers, [ 267,268 ] peptide‐based supramolecular polymers chemically linked to spiropyran‐based networks, [ 269 ] poly‐catenanes, [ 270 ] peptoid‐based nanomaterials, [ 271 ] supramolecular macrocycle fibers, [ 272 ] responsive conjugated polymers, [ 273 ] platinum complexes, [ 274,275 ] supramolecular polymer hydrogels, [ 276 ] and light‐harvesting double‐walled nanotubes. [ 277 ]…”
Section: Example Applicationsmentioning
confidence: 99%
“…3,4,6,9,58 Based on various sequence-structure analyses, nowadays, both the rational design and the computer-aided structure prediction of peptoid foldamers is possible. 1,5,115,[130][131][132][133][134]…”
Section: Combinatorial Libraries For the Discovery Of Peptoid Foldamersmentioning
confidence: 99%